The Effect of Discovery Learning on Students’ Higher-order Thinking Skills - Thira Thifa al Aliyawinata; Enggar Utari; Mahrawi Mahrawi (International Journal of Biology Education Towards Sustainable Development, 2021)
This study aims to determine whether the Discovery learning model can affect the students' High Order Thinking Skills (HOTS) ability in the blood circulation system. This research was conducted by assessing the cognitive aspects of students, analyzed by descriptive methods using instruments in the form of essay questions and learning observation sheets. The method used in this study is a weak experiment. The subject in this study is 38 students at one high school in Indonesia. Based on the research results, the Discovery Learning model affects the students' High Order Thinking Skills (HOTS) ability by increasing the average pretest score of 52.23 to 69.47 in the average posttest score. Wilcoxon test results obtained asymp. sig. (2-tailed) 0.000 0.05, then H0 is rejected and it can be concluded that there is a difference in the average student learning outcomes between the pretest and posttest. it can be concluded, Discovery Learning model can affect the ability of High Order Thinking Skills (HOTS).